Natural orifice transesophageal endoscopic surgery: state of the art - Moreira-Pinto, J (2013)
The main goal of Natural Orifice Transluminal Endoscopic Surgery (NOTES) is performing surgery avoiding skin incisions. Theoretical advantages of NOTES include decreased postoperative pain, reduction/elimination of general anesthesia, improved cosmetic outcomes, elimination of skin incision-related complications such as wound infections and hernias, and increased overall patient satisfaction. Although various forms of port creation to accomplish thoracic NOTES procedures have been proposed, transesophageal NOTES has been shown to be the most reliable one. The evolution of endoscopic submucosal transesophageal access resulted in the development of per-oral endoscopic myotomy (POEM), which had a fast transition to clinical practice. The authors present a review of the current state of the art concerning transesophageal NOTES, looking at its potential for diagnostic and therapeutic interventions as well as the hurdles yet to be overcome.